Development and application of hybrid SOL-GEL materials for microoptics - Jiang, Hongjin (2008)
SiO2/TiO2 binary sol-gel materials have been developed with the organic modified silicate MAPTMS trimethoxysilane. Sol-gel derived radiation sensitive material has been exploited to fabricate miniature optic devices, and fabrication parameters have been studied and discussed.